2000
DOI: 10.1103/physrevstab.3.034201
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of simulated and observed beam profile broadening in the Proton Storage Ring and the role of space charge

Abstract: Transverse beam profiles are observed to broaden with increasing intensity in the Proton Storage Ring at the Los Alamos Neutron Scattering Center. Measured profiles are simulated with an H 2 injection model that includes a 2D particle-in-cell space charge calculation. Inclusion of space charge effects in the simulation improves the agreement between the experimentally observed profiles and the calculated profiles. The comparisons are made for a range of injected intensities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 3 publications
2
17
0
Order By: Relevance
“…In some accelerators where synchrotron motion is negligible (in the SNS the full injection process of 1000 turns takes about one synchrotron oscillation), it seems reasonable to expect that an impact of the synchrotron motion will not be important. In fact, some recent experiments and simulations for the bunched beam in the LANL PSR, where there is slow synchrotron motion similar to the SNS, seem to support the above discussion [16,17,22]. Here we explore these effects for machines with slow synchrotron motion using a realistic beam of the SNS.…”
Section: Bunched Beams and Multiturn Injectionsupporting
confidence: 55%
See 1 more Smart Citation
“…In some accelerators where synchrotron motion is negligible (in the SNS the full injection process of 1000 turns takes about one synchrotron oscillation), it seems reasonable to expect that an impact of the synchrotron motion will not be important. In fact, some recent experiments and simulations for the bunched beam in the LANL PSR, where there is slow synchrotron motion similar to the SNS, seem to support the above discussion [16,17,22]. Here we explore these effects for machines with slow synchrotron motion using a realistic beam of the SNS.…”
Section: Bunched Beams and Multiturn Injectionsupporting
confidence: 55%
“…For the split-tune case, an experiment was recently performed at the LANL PSR [22]. Subsequent numerical simulations confirmed that the observed beam broadening is due to the coherent half-integer resonance [16].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, careful attention was paid to lattice settings, injection, painting, and RF scenarios. These simulations gave good agreement with the measured beam profiles [2], both showing a systematic broadening in the vertical direction at high intensities. Subsequent analysis of the simulations suggested that the profile broadening is related to the half integer resonance at Q y = 2 (the bare tune was Q y = 2.14) [3].…”
Section: Introductionsupporting
confidence: 76%
“…In an earlier study [11], the space charge dynamics of a high intensity synchrotron beam were explored through a particle core model approach that included the effects of lattice structure and finite momentum spread. Previous work with PSR data demonstrated successful benchmark of a number of experimental beam profiles [12] using the ORBIT particle-in-cell (PIC) tracking code [13,14]. The beam profile broadening at high intensity was observed in these studies, but no attempt was made to explore the physics behind the broadening; such an attempt was previously begun but not completed [4].…”
Section: Introductionmentioning
confidence: 96%